Legal Certainty and Transparency in the Implementation of Government-Private Public Partnerships in Indonesia - Stevy Hanny Supena; Muh. Ilham; Eko Budi Santoso; Petrus Polyando (Faculty of Law, Universitas Pekalongan, 2025)
Indonesia's public-private partnerships (PPP) have become a key strategy to address infrastructure development challenges and other vital sectors. While PPPs have significant potential to drive sustainable economic growth, their implementation in Indonesia still faces various challenges, particularly concerning legal certainty and transparency. This study examines the challenges encountered in PPP execution, focusing on legal and transparency issues in project management. Based on the analysis of several case studies related to PPP, such as geotourism development in Belitong, the impact of the pandemic on export sectors, and the strengthening of immunization systems, the research identifies how public-private collaboration can significantly contribute to sectors like tourism, economy, and healthcare. However, major challenges include unclear regulations regarding the allocation of risks, rights, and responsibilities between the parties involved and a lack of effective transparency mechanisms in project management. This study also analyzes existing regulations, such as Law No. 2 of 2017 on Construction Services and Presidential Regulation No. 38 of 2015, and discusses the need for revisions and improvements. The findings suggest that, for PPP projects to succeed and be sustainable, strengthening legal frameworks and improving transparency are essential, ensuring that the collaboration between the government and the private sector operates more efficiently and maximally benefits Indonesia's development.